The Influence of Different Pretreatment Methods of Highland Barley by Solid-State Fermentation with Agaricus sinodeliciosus var. Chaidam ZJU-TP-08 on Its Nutrient Content, Functional Properties and Physicochemical Characteristics - Biao Liu; Hongyun Lu; Qin Shu; Qihe Chen; Jinling Wang (Journal of Fungi, 2022)
To enhance the nutritional value of highland barley (HB), this work investigated the effects of solid-state fermentation (SSF) by Agaricus sinodeliciosus var. Chaidam ZJU-TP-08 on nutrient content, phenolic components, antioxidant activities, and physicochemical characteristics of HB upon different pretreatments (germination, ultrasound and soaking). The results showed that germinated highland barley (GHB) exhibited higher levels of ergosterol (0.19 ± 0.01 mg/g) in all fermentation groups. The content of β-glucan was higher in the SSF-GHB, with an increase of 24.21% compared to the control. The content of total amino acids, dietary fiber, total phenols and flavonoids were higher in the fermentation HB pretreated by ultrasound, increasing respectively by 5.60%, 61.50%, 25.10% and 65.32% compared to the control group. In addition, the colonized HB exhibited excellent physicochemical characteristics, including increased water solubility index and decreased pasting characteristics. Herein, the nutritional value and the biological activities were enriched in the pretreated HB through SSF, indicating its potential application for nutrition-enriched functional foods.